Decisão de participação dos jovens brasileiros no mercado de trabalho : análise com base em características individuais e familiares - Costa, Miqueline Leite (2021)
In 2014 a crisis began in the country that associated low economic dynamism with persistent problems in the labor market. In 2019, the age group of people who participated in the Economically Active Population (PEA) and which recorded the highest percentages of unemployment was between 14 and 24 years old. For many young people, not participating in the PEA is not an option: as age increases, so do the opportunity costs of just continuing to study. With the crisis, adds to this fact the effect of the additional worker. It is noteworthy that although several factors have contributed to the increase in the PEA of young children aged between 14 and 24 years, the variation in this participation was negative in the period. The aim of this study was to analyze the evolution of the participation of young children aged between 14 and 24 years in the labor market, considering individual characteristics and family interactions. With this objective, we sought to answer the following research problem: how are family interactions and problems in the Brazilian labor market affecting the decisions of participation of young between 14 and 24 years of age in the labor market? The database used in this study was the microdata from the National Household Sample Survey (PNAD) Continuous, released quarterly by the Brazilian Institute of Geography and Statistics (IBGE), and the applied methodology was a panel logit econometric model. Two hypotheses were tested in the study and with the investigation it was verified a smaller participation in the job market over time by the young people, but not only this, there was also variation in participation considering most of the variables analyzed and in most cases the changes, especially from 2014 onwards, were caused by the crisis. It was also found that it is not possible to state that some characteristics can define the participation of young people in the labor market in isolation, despite recognizing the great influence exerted by family characteristics, as was the case with income. It is noteworthy, however, that different variables exert great influence on this decision: age, years of education, male gender, increase in the number of household members, young people from lower-income families, living in the South and Center regions -West and Southeast, in comparison with the North region, as well as occupation or performance of work by the responsible family, which contributed with positive average marginal effects for the participation of young people in the labor force The effects were influenced by variables such as: living in an urban area, being in families in the income groups, being from the Northeast region of the country or having the presence of an elderly person at home or yet resides in a family with high level of education of the family responsible. As a contribution of this work, the use of the logit panel model stands out, based on the division of labor not only between spouses, without considering the other family members, but mainly considering in this division the work decision of the young children.